Hubungan Antara Volume Prostat dan Risiko Chronic Kidney Disease (CKD) pada Pasien Benign Prostate Hyperplasia (BPH) Pasca Transurethral Resection of the Prostate (TURP): Sebuah Studi Observasional - Besut Daryanto; Maghfirah Nur Afifah; Taufiq Nur Budaya (Majalah Kedokteran Indonesia, 2024)
Introduction: Benign Prostate Hyperplasia (BPH) is an enlarged prostate gland that causes problems in micturition and results in disruption of urine flow. Factors that cause prostate enlargement from a combination of chronic and progressive urine retention, high bladder pressure and ureterohydronephrosis can cause progressive kidney injury. The obstructive process changes the cells and physiological conditions in the bladder muscle and collagen contributes to increasing bladder pressure and the inability to empty the bladder and ends up causing kidney failure. This study was to determine the prevalence of chronic kidney disease (CKD) in BPH patients undergoing transurethral resection of the prostate (TURP) surgery.Method: Using non-probability sampling method with consecutive sampling technique. Data were analyzed by univariate analysis using data frequency tables and bivariate analysis using the chi-square test.Result: Of the total 178 BPH patients, 15 of them suffered from CKD (8.4%). BPH prevalence was highest in the age category 61-70 (39.3%), the majority had prostate volume greater than 50 ml (59%), the most common symptoms were severe lower urinary tract symptoms (LUTS) (83.1%) and urine retention (74.7%), some of them were accompanied by comorbidities such as hypertension (33.7%). The most common indication for surgery in patients who underwent TURP was recurrent retention (79.2%). The chi-square test showed an association between BPH and the incidence of CKD.Conclusion: The prevalence of CKD at all stages in BPH patients who underwent TURP surgery was 8.4%. The most influential factors for the occurrence of CKD in BPH patients are prostate volume 30-40 ml, prostate volume 41-50 ml, and men aged 71-80 years.